Gilt das Stereotyp der polnischen Wirtschaft immer noch? Zu den Veränderungen in Polen aus imagologischer Perspektive - Zator-Peljan, Joanna (Glottodidactica, 2013)
The main focus the paper investigates concerns Polish-German relations from the perspective of imagology. The author of the article concentrates on the stereotype of the polish economy and compares it with the imagological standpoint by analyzing two chosen publications: „Viva Polonia. Als deutscher Gastarbeiter in Polen” by Steffen Möller and „Polen” by Thomas Urban. The above-mentioned analysis should lead to an answer for the following question: can the way of perceiving of the Polish economy be modified by means of well-known authors?